Investigating Multiplicity: Institutional Logics and Division II Commuter Student Athletes - Jay Martyn; Brent D. Oja; Alan L. Morse (University of Kansas Libraries, 2020)
The primary purpose of this study was to examine the perceptions of commuter student athletes who were hypothesized to experience a multiplicity of institutional logics while competing at the NCAA Division II level. Second, if multiple competing logics were present, the authors intended to test a theoretical model of logic multiplicity development. Utilizing a case study methodology, the authors collected data from commuter student athletes competing at the Division II level. The study's findings indicated that commuter student athletes perceived the presence of multiple competing logics and that these logics indicated an aligned or minimally estranged organization. In particular, the high compatibility and high centrality of multiple competing logics signified an organization aligned between academic, athletic, and family values, whereas the low centrality and low compatibility of social identification and societal factors denoted an estranged organization for commuter student athletes. The implications of this research within sport management are presented herein.